2020
DOI: 10.1111/anec.12752
|View full text |Cite
|
Sign up to set email alerts
|

PR depression with multilead ST elevation and ST depression in aVR by left circumflex artery occlusion: How to differentiate from acute pericarditis

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“… 20 In a few studies, the PR segment was evaluated in acute myocardial infarction (MI) which showed PR segment depression may be seen in circumflex artery occlusion. 21 In addition, this may be used as a predictor of heart block in inferior MI. 22 The PR segment was not evaluated in the patients with PH in the previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 20 In a few studies, the PR segment was evaluated in acute myocardial infarction (MI) which showed PR segment depression may be seen in circumflex artery occlusion. 21 In addition, this may be used as a predictor of heart block in inferior MI. 22 The PR segment was not evaluated in the patients with PH in the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The PR segment has received more attention in pericarditis which present with diffuse PR segment depression 20 . In a few studies, the PR segment was evaluated in acute myocardial infarction (MI) which showed PR segment depression may be seen in circumflex artery occlusion 21 . In addition, this may be used as a predictor of heart block in inferior MI 22 .…”
Section: Discussionmentioning
confidence: 99%
“…signs of acute pericarditis are P.R.-segment distress (found rarely), multi-lead S.T. segment rise, and S.T.-segment distress in the lead named aVR [ 29 ].…”
Section: Reviewmentioning
confidence: 99%
“…• In STEMI, depression of the PR segment in the inferior wall is a prognostic criterion (≥1.2 mm) associated with atrioventricular block, supraventricular arrhythmias, and rupture of the free wall with a consequent increase in mortality in 1 year 19,20 .…”
Section: Atrial Infarctionmentioning
confidence: 99%